'Going global': comparing access to global learning experiences in the online social networks of Turkish-Dutch, Moroccan-Dutch, and native-Dutch youth. Issue 2 (4th March 2021) - Kommers, Suzan; de Haan, Mariëtte
ABSTRACT: This paper addresses the potential of online environments as spaces for young people to develop intercultural competences by studying how otherness is created online and how this holds potential for learning. While online communication is an increasing part of young peoples' lives, not much is known about how young people use their online social networks to connect with culturally diverse others and whether such interactions create opportunities for learning. Using social network analyses and discourse analyses of self-reports, we compared Turkish-Dutch, Moroccan-Dutch and native-Dutch youth regarding: 1) the geographical dispersion and ethnic diversity of their online social networks and 2) how they reported on their online interactions and the opportunities for global learning. Young people from these communities differed in how they connected online and how they reflected on interactions in which they were confronted with different perspectives. We suggest a re-examination of the notion of global learning, paying more attention to the highly varied experience of 'global' youths' perception of interactions with different others, as well as what the learning potential of 'going global' entails.